ZAMBIA: PRIVATE SECTOR INVESTMENT IN SECURITY OF LAND TENURE. FROM PILOTING USING TECHNOLOGY TO NATIONAL ROLLOUT - Emmanuel Tembo,; Didier Sagashya (African Journal on Land Policy and Geospatial Sciences, 2022)
Context and background